A three-layer parallel computing system for shipbuilding project scheduling optimization. (October 2017) - Han, Duanfeng; Yang, Boxin; Li, Jinghua; Sun, Miaomiao; Zhou, Qinghua; Wang, Jiaxuan
To solve the large-scale scheduling problem more efficiently within the requirements of the contract in shipyard, a three-layer parallel computing system was proposed. An optimized model for shipbuilding project scheduling problem was constructed under the condition of taking time and resource constraints into account. Moreover, the key techniques of proposed system were elaborated and the main steps were designed. In the first computing layer, the problem was decomposed into small parts in heterogeneous systems, reducing the problem scale; then, in the second layer, a co-evolution strategy for multi-populations was put forward to improve the algorithm robustness; in the third layer, a massive parallel computing method was performed under the Graphic Processing Unit structure. Finally, through two simulation examples, the robustness and outperforming others of the improved algorithm were verified.